Religious Nation State: Bahtiar Effendy and Islamic Political Thought - Ali Akhbar Abaib Mas Rabbani Lubis (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2020)
This paper discusses the thoughts of Bactiar Efendy in his work entitled Islam and the State; Transforming Islamic Political Thoughts and Principles in Indonesia, to see the relevance and reflection of his thoughts on the relationship between Islam and the State. This paper is included in the cluster of qualitative research involving library research. This study uses data analysis conducted after a set of library documentation is obtained, then the data is analyzed and analyzed including data reduction, data display, and conclusion making. The research results obtained in this paper that Bahtiar Effendy is a Muslim scholar and professor of political science at UIN Syarif Hidayatullah Jakarta and Chairman of PP Muhammadiyah. The relevance and reflection of his thoughts on political Islam in Indonesia in his work do not consider secularization between Islam and the State as the best solution, instead, the contribution of Bahtiar Effendy's thought to a shifting of paradigm on Islamic politics from what previously led to formalism-legalism is shifting to substantialism, without the need to be forced make an Islamic state but enough to provide the substance of the teachings (ethical/moral), then the Indonesian state deserves to be called a religious nation-state.